مقام اللغة في الشعر الصوفي قراءة في ديوان صحوة الغيم لـ: عبد الله العشي - دهيلي, نسرين (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
يدخل الشاعر غمار التكوين الشعري وعدّته الوحيدة اللغة كلا وأجزاء، حروفا وجملا، تأسره قدرتها على نقل شعوره وتصوير خياله، وترجمة أحاسيسه، فيأتيها فرادى وجماعات، يتجسد من خلالها ويتفنن في تشكيلها، لتعبر عن حالاته وأحواله المختلفة، وتنوب عنه في فنّ القول إذ هي القول ذاته، ولا نصبح مع هذا النوع من النصوص -الممثل في هذه الدراسة بديوان صحوة الغيم- أمام لغة الشعر وإنّما أمام شعر اللغة، فتتغير الرؤى وتختلف الإشكالات ويصبح السؤال المعهود: كيف قال الشاعر ما قال؟ هو سؤال اللغة: كيف استطاعت أن تتمثل ماذا يريد وما هي طريقته في القول الشعري؟. ومن هذا المنطلق تكتسب اللغة أهميتها في هذه الدراسة، وفي تشريح النص الشعري المعاصر، الصوفي على وجه الخصوص، وتصبح قراءتها إجمالا وتفصيلا، متصلة ومنفصلة، خلايا صوتية أو كائنات جُمَلِيَّة ونصية هي المُعوَّل عليه لبناء الدلالة وقراءة النص. Summary :    Poet enters to the adventure of poetic composition, his only kit is the language using everything: its alphabet and sentences, which has the ability to convey his emotions, draw his fiction as well as interpret his feelings, so the poet comes to it individually and in groups in order to be creative in forming it to reflect his different cases and conditions thus it replaces him in the saying if we don’t say it is the saying itself.   We won’t become in this kind of texts in front of the language of poetry but the poetry of the language like: “SAHWAT ALGHAYM” which is represented in this study ,so the points of view and questions will be changed to the common question that is How and what does the poet say? It’s the question of the language .How can the language represent the poet , what he wants to say and what is  his way in poetic saying? From this point the language is gaining importance in this study and in the analysis of contemporary poetic texts even mystic in particular. Its reading becomes in general and details connected and separated in this case the reader focuses on sounds and sentences “all the language” to understand the meaning of the text.